TFMCC vs ASMP: Lessons learned from performance evaluation - Christos Bouras; Apostolos Gkamas; G Kioumourtzis (International Journal of Network Management, Wiley InterScience, 2012)
In this article we present a simulation-based comparison of one of the best-known multicast congestion control schemes—TCP-friendly Multicast Congestion Control (TFMCC)—against our proposed Adaptive Smooth Multicast Protocol (ASMP). ASMP consists of a single-rate multicast congestion control mechanism which takes advantage of the RTCP Sender (SR) and Receiver Reports (RR) in order to adjust the sender?s transmission rate in respect of the network conditions. The innovation in ASMP lays in the ?smooth? transmission rate, which is TCP-friendly and prevents oscillations. We use an integrated simulation environment named Multi- Evalvid-RA for the evaluation of the two congestion control schemes. Multi-Evalvid-RA provides all the necessary tools to perform simulation studies and assess video quality by using both network-centric metrics along with video quality measurements. Performance evaluation results show that ASMP is a very efficient solution for rate-adaptive multimedia applications and a serious competitor to well-known TFMCC.